Deskripsi Wilayah, Kebudayaan dan Sejarah Pemerintahan di Wawonii Menurut Arsip-Arsip Kolonial - Hasdairta Laniampe; La Niampe; Syahrun Syahrun; Rahmat Sewa Suraya; Hisna Hisna; Alias Alias (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
The preparation of a description of the territorial, cultural, and administrative history of Wawonii is an important endeavor to explore and assemble information from valuable colonial archives to understand better this important aspect of the region's history, culture, and administration. Through collecting and analyzing historical documents, administrative reports, colonial newspapers and official records related to Wawonii, this research aims to map the geography, ecology and structure of Wawonii during the colonial period and how these changes have influenced its current state. In addition, focus is also given to exploring traditions, beliefs, language, art, and other cultural aspects that influenced Wawonii society during the colonial period. Highlighting administrative structures, the role of local leaders, political dynamics, and the implementation of colonial policies are important in explaining the history of governance in Wawonii.